Pengembangan Media Pembelajaran Biologi Menggunakan Aplikasi Camtasia - sari, indah karunia; Tanjung, Indayana Febriani; Adlini, Miza Nina (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
This study aims to determine the validity, practicality, and effectiveness of biology learning media using the Camtasia application which was developed in the form of learning videos on the subject of the human circulatory system. This study uses the Research and Development (R&D) method, with the ADDIE model namely analysis, design, development, implementation, and evaluation. The instruments used were media and material expert validation sheets, teacher and student response questionnaires, and multiple choice tests to assess student effectiveness. The developed media has an average overall media validity score of 0.83 which indicates that it meets the valid criteria. It is said to be "valid" according to the validity criteria (V > 0.8). The average response of teachers and students to each aspect of learning media shows a useful value of 3.90, this shows that the media and all responses of teachers and students fulfill the practical value criteria. For the value of effectiveness, 91 percent of students meet the value of the effectiveness criteria of 79.1 seen from the learning outcomes assessment test. This study shows that biology learning media fulfills the valid, practical, and effective requirements. so that it is expected to be used as a learning resources. Keywords: Development, Learning Media, Video, Camtasia.